2014
DOI: 10.1111/ejn.12716
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sensorimotor gating following selective lesions of cholinergic pedunculopontine neurons

Abstract: Sensorimotor gating is the state-dependent transfer of sensory information into a motor system. When this occurs at an early stage of the processing stream it enables stimuli to be filtered out or partially ignored, thereby reducing the demands placed on advanced systems. Prepulse inhibition (PPI) of the acoustic startle reflex (ASR) is the standard measure of sensorimotor gating. A brainstem-midbrain circuitry is widely viewed as mediating both PPI and ASR. In this circuitry, the pedunculopontine tegmental nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 66 publications
1
27
0
1
Order By: Relevance
“…Lesion studies of prepulse inhibition indicated a role for the pedunculopontine tegmentum (PPT), a cholinergic nucleus of the mesopontine [40]. However VACht knockouts have normal PPI [3] and selective ablation of cholinergic PPT neurons failed to disrupt prepulse inhibition [2]. Despite uncertainty as to the circuit basis of prepulse inhibition in mammals, there is reason to posit that a homologous presynaptic inhibition pathway is involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion studies of prepulse inhibition indicated a role for the pedunculopontine tegmentum (PPT), a cholinergic nucleus of the mesopontine [40]. However VACht knockouts have normal PPI [3] and selective ablation of cholinergic PPT neurons failed to disrupt prepulse inhibition [2]. Despite uncertainty as to the circuit basis of prepulse inhibition in mammals, there is reason to posit that a homologous presynaptic inhibition pathway is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Classic rodent studies argued for a central role of a mesopontine cholinergic projection to the pontine nucleus caudalis (PnC), however this pathway has recently been ruled out by the failure to produce PPI deficits in vacht knockouts or after selective cholinergic neuron lesions [2,3]. Prepulse inhibition is found across vertebrates, making it possible to use simpler models such as zebrafish to identify the underlying cellular pathways [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, excitotoxic as well as selective urotensin II/diphtheria toxin pedunculopontine cholinergic lesions lead to deficits in sustained attention and acoustic startle responding. A selective loss of pedunculopontine cholinergic neurons reduced this to the point where it was not detectable, but when intertrial intervals were long enough appropriate responding was seen . This returns the cholinergic neurons to a more prominent ascending reticular activing system function, maintaining vigilance and alertness (compatible with a role in behavioral state control) leaving the noncholinergic neurons apparently with greater responsibility for the more basal ganglia–like problems of action selection and learning (although these of course will also benefit from appropriately targeted attention mediated by pedunculopontine cholinergic neurons).…”
Section: Differentiation In the Pedunculopontine: Which Neurons Do What?mentioning
confidence: 99%
“…It has the capacity to deliver fast sensory data with value already partly assessed to effect corticostriatal processing. In parallel, it is likely that pedunculopontine cholinergic neurons have a simultaneous role in focusing attention and initiating a rapid response to imperative signals . The pedunculopontine clearly directs output into forebrain systems, but in addition it projects to motor and associated autonomic control sites lower in the brain stem, allowing regulation of key motor, respiratory, and cardiovascular sites that are involved in the production of rapid responses to imperative stimuli.…”
Section: A Functional Hypothesismentioning
confidence: 99%
“…The genetic fusion of urotensin II (UII) and the ribosome inactivating protein diphtheria toxin (Dtx) creates a recumbent protein toxin (Dtx-UII) which, when directly infused into the PPTg, selectively destroys cholinergic neurons (Clark et al 2007). Using this toxin, it has recently been found that the deficits in sensorimotor gating (measured with prepulse inhibition) following excitotoxic damage to the PPTg are not present after selective depletion of the cholinergic neuronal subpopulation (MacLaren et al 2014a). Here, we used this toxin to assess specifically the contributions of cholinergic neurons within pPPTg to instrumental learning and the locomotor response to systemic nicotine.…”
Section: Introductionmentioning
confidence: 99%